Promoting development - Griesgraber, Jo Marie(ed.); Gunter, Bernhard G.(ed.) (London, 1995)
In the wake of the 50th anniversary of the founding of the World Bank and the IMF, and as we approach the next century, a review of the Bretton Woods institutions is urgently needed. This collection presents practical, wholly feasible suggestions for reform of the international financial bodies and the United Nations aid and trade agencies. Beginning with Sir Hans W. Singer's historical assessment of the subject, the contributors to this volume seek to implement in policy and practice the results of their academic research. Norman Girvan addresses the underlying dynamics between borrowing countries and donors; Reginald Herbold Green sets attainable trajectories in reforming the global economic institutions; Katarina Tomasevski argues for the institutionalisation of Human Rights Impact Assessments and Lourdes Urdaneta-Ferrán reviews statistics used and produced by the major international institutions.
Keywords: Financial institutions